Causes and Impacts of Organized Crime in Latin America : Comparison of Mexico and Chile - Bee, Lucia; Sejkora, Jiří, 1985-; Proch, Dominik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The aim of this thesis will be to find out, by comparing the causes, impacts, and means, why Mexico is worse off (compared to Chile) when it comes to organized crime. The comparison will be made on various levels (economic, political, and socio-cultural). Each sector will compare different indices and values to best capture the problem and explain why there is such a big difference within one region. The theoretical part will describe the main concepts related to organized crime, its characteristics, and typology, but also the theoretical overview of causes, impacts, and means of fighting organized crime. In the empirical part of this thesis, the given theory will be applied to the specific case of Mexico and Chile.
Vedoucí práce: Jiří Sejkora
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor dipl. práce]; diplomové práce; master's theses